Public investment as commitment - Reyer Gerlagh; Matti Liski (Center for Economic Studies and ifo Institute (CESifo), 2011)
Should public assets such as infrastructure, education, and the environment earn the same return as private investments? The long-term nature of public investments provides commitment to current preferences, which justifies lower than private returns for time-inconsistent decision markers. An institutionalized (i.e., exogenous) rule demanding equalized comparable returns removes the bias and implements the standard cost-benefit requirement. We show that such a stand-alone rule has no general welfare content: it implements Pareto efficiency if and only if preferences are time-consistent. Efficiency requires rules not only for the composition of investments but also for overall savings. Without supplementary rules for savings, accepting lower returns for long-term public assets is welfare improving.
Keywords: H43; H41; D61; Q54; E21; 330; public investments; cost-benefit analysis; inconsistent preferences; Öffentliche Investition; Kosten-Nutzen-Analyse; Zeitkonsistenz; Wohlfahrtseffekt; Theorie